Impact of dexamethasone added to intra-articular morphine and bupivacaine for postoperative analgesia after knee arthroscopy - Heba Fouad Toulan (SpringerOpen, 2021)
Abstract Background Pain relief after knee arthroscopy is very important for early recovery and rehabilitation. The study was conducted to evaluate the effects of adding dexamethasone (8 mg) to intra-articular morphine (10 mg) and bupivacaine (25 mg) combination on postoperative pain after knee arthroscopy. Results We enrolled 40 patients, 18–65 years-old of both sexes, ASA I and II scheduled for minor arthroscopic knee surgeries. The study group showed a lower visual analog score at rest and movement, prolonged postoperative analgesia, and decreased total analgesic consumption compared with the control group (P value < 0.05). Conclusions Adding dexamethasone to intra-articular combination of morphine and bupivacaine after knee arthroscopy prolongs the duration of analgesia, lowers pain scores, and decreases total analgesic consumption with no detected adverse effects.